ALTERNATIVAS PARA MAIOR AGREGAÇÃO DE RENDA EM UNIDADES DE PRODUÇÃO AGROPECUÁRIA DO MUNICÍPIO DE IJUÍ / RS - Titzmann, Aline K.; Uhde, Leonir T.; Garcia, Dagmar C.; Fernandes, Sandra B. V.; Carbonera, Roberto (Salão do Conhecimento, 2013)
Resumo